Characterization of poloxamers by reversed-phase liquid chromatography. Issue 13 (16th March 2016) - Guan, Bing; Ali, Amr; Peng, Haofan; Hu, Weiwei; Markely, Lam Raga; Estes, Scott; Prajapati, Shashi
Abstract : We developed a novel reversed-phase liquid chromatography method for monitoring multiple ingredients in poloxamers and evaluating their stability. Abstract : Poloxamer 188 plays a critical role in protecting cells during cell culture bioprocessing. To better understand the properties of poloxamers, a reversed-phase liquid chromatography (RPLC) method was developed to characterize the ingredients in poloxamers. A Waters SunFire C18 column gave good separation of ten poloxamer ingredients, which were monitored by using an ultraviolet (UV) detector at 200 nm and an evaporative light scattering detector (ELSD). UV detection of less hydrophobic ingredients showed good linearity and precision of the selected poloxamer ingredients. Furthermore, nine fractions were isolated from a single poloxamer 188 lot, and the molecular weights of all the fractionated ingredients were evaluated by size exclusion chromatography (SEC). This RPLC method can detect the variation not only among different types of poloxamers, but also among different lots of the same poloxamer. In addition, this RPLC method can be used to measure the stability of some poloxamer ingredients under various conditions.